Short-cavity random distributed feedback fiber laser with ultra-low threshold. (11th December 2019) - Cai, Yao; Wu, Jiadong; Deng, Zhixiang; Liu, Jun; Chen, Yu
Abstract: We experimentally demonstrated a random distributed feedback fiber laser (RDFB-FL) with an ultra-low threshold, utilizing a highly nonlinear optical fiber (HNLF). A piece of HNLF was used as the random laser gain medium to resolve the contradiction between the lasing threshold and cavity length. Consisting of a half-open cavity structure, the proposed RDFB-FL had a lasing threshold as low as 0.408 W (record low) with a relatively short cavity length of 850 m. In a ring cavity, the lasing threshold could be further reduced to 0.284 W with a cavity length of 950 m by the combined action of distributed feedback and cavity feedback.